2009
DOI: 10.1007/s00428-009-0846-3
|View full text |Cite
|
Sign up to set email alerts
|

Localization of indoleamine 2,3-dioxygenase in human esophageal squamous cell carcinomas

Abstract: Immunosuppressive factors derived from the tumor and nontumor cells present in the tumor microenvironment contribute to tumor escape from host immune attack. Recently, the tryptophan-catabolizing enzyme indoleamine 2,3-dioxygenase (IDO) derived from both the tumor cells and surrounding nontumor cells was found to function as a critical immunosuppressive factor. While the expression of IDO is intensively under investigation in many types of cancers, little information is available in esophageal squamous cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 45 publications
3
12
0
1
Order By: Relevance
“…Moreover, our data indicated that the expression of IDO correlated with the poor clinical outcome of ESCC patients and are consistent with a previous study that ESCC patients with higher levels of IDO expression had a worse survival rate than patients with lower levels of IDO expression [24]. However, these results were in contrast with those of Liu et al in that IDO expression was not significantly correlated with clinical outcomes [25]. The less marked impact of IDO on clinical outcomes reported by Liu et al might be due to the comparatively small patient population analyzed.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, our data indicated that the expression of IDO correlated with the poor clinical outcome of ESCC patients and are consistent with a previous study that ESCC patients with higher levels of IDO expression had a worse survival rate than patients with lower levels of IDO expression [24]. However, these results were in contrast with those of Liu et al in that IDO expression was not significantly correlated with clinical outcomes [25]. The less marked impact of IDO on clinical outcomes reported by Liu et al might be due to the comparatively small patient population analyzed.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Liu reported that the level of IDO expression did not correlate with the clinic outcomes of ESCC patients [25]. In the current study, we investigated the relationship between IDO expression and the degree of tumor infiltration of CD8 + T cells, and the clinical significance of IDO expression in ESCC.…”
Section: Introductionmentioning
confidence: 81%
“…Enhanced expression of IDO1 is observed in esophageal carcinoma and its expression correlates with poor survival 138, 139 . IDO1 expression correlated with a lower number of tumor infiltrating lymphocytes 139 .…”
Section: Other Gastrointestinal Cancersmentioning
confidence: 99%
“…DCs in the tumor stroma are exclusively CD208-positive mature DCs, while DCs which infiltrated into ESCC epithelium are predominately CD1α-positive immature DCs [22]. Furthermore, we have also found that some of the DCs in ESCC stroma can express the tryptophan-catabolizing enzyme IDO [23], which has been shown to be a critical factor in inducing T cell tolerance and promoting cancer progression in various human cancers. Such alternation in microenvironmental is a common event in many types of SCCs, and the investigation of microenvironmental changes in ESCCs may have a widely clinical significance [5,6,17,24].…”
Section: Introductionmentioning
confidence: 84%
“…ESCC patients with higher number of NK cells have a better prognosis than those with lower [6], and NK cell dysfunction in ESCCs is with down-regulated CD16 and up-regulated CD56 molecules [21]. Moreover, we have previously examined the dendritic cell (DC) [22] and immune suppressive factor indoleamine 2,3-dioxygenase (IDO) [23] in the tumor microenvironment of ESCCs. Our results revealed that the cellular characterization of DCs residing in the tumor stroma was different from those DC cells which infiltrated into ESCC malignant epithelium.…”
Section: Introductionmentioning
confidence: 97%